Nonstationarity of drought characteristics in some parts of Syrian costal region during the period 1960-2016 - سكاف, ميشيل; بركات, راما (Latakia University Journal -Biological Sciences Series, 2021)
Drought events are characterized by a continuous decline of water availability and an increase in evaporative demand. Monthly rainfall and maximum and minimum temperatures data for three meteorological stations (Lattakia-Tartous-Safita) were used to evaluate drought characteristics in Syrian costal region during the period 1960-2016. Water Balance Anomaly Index (WBAI) was applied to identify drought at the rainy season (from September to June) and monthly time scales (from November to June) using monthly sliding windows (precipitation amount of current month and the previous two months). Trends with mann-kendall test were used to detect significant changes in drought index values at different time scales, and to detect changes in drought duration with different intensities. Logistic distribution and descriptive analysis were utilized to compare drought frequency and probability of its occurrence at two study periods: 1960-1988 and 1988-2016. Results showed increasing drought intensity at annual and monthly time scales from December to June, and an increment of severe and extreme dry periods, with enhancement in duration of consecutive dry months. Furthermore, drought frequency and probability of dry years had increased in the last decades. Our findings imply changes in drought intensity duration and frequency in the three studied stations during the second half of the study period, and this will pose big challenges for water resources management, agricultural production and ecosystems protection against pathogens, insects and forest fires.